2002
DOI: 10.1111/j.1530-0277.2002.tb02494.x
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Transfer in Children with Heavy Prenatal Alcohol Exposure

Abstract: These findings suggest that children with heavy prenatal alcohol exposure display subtle deficits in the interhemispheric transfer of information in the somatosensory domain. Such deficits in interhemispheric transfer are likely to be related to the myriad of other behavioral and cognitive impairments observed in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 61 publications
(63 reference statements)
8
43
1
Order By: Relevance
“…Furthermore, another study observed regional brain metabolic alterations in adolescents and young adults with FASD relative to controls, including altered metabolism of the CC (Fagerlund et al, 2006). Well in keeping with these findings, subtle functional deficits in interhemispheric transfer and bimanual coordination (i.e., tasks sensitive to a functional CC) have been observed at the behavioral level (Roebuck-Spencer et al, 2004;Roebuck et al, 2002). Given the particular vulnerability of the CC in FAS/FASD, and presuming that dichotic listening asymmetry relies on the functional status of the CC, we expected the children with FAS in the present study to demonstrate atypical auditory lateralization during dichotic listening.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, another study observed regional brain metabolic alterations in adolescents and young adults with FASD relative to controls, including altered metabolism of the CC (Fagerlund et al, 2006). Well in keeping with these findings, subtle functional deficits in interhemispheric transfer and bimanual coordination (i.e., tasks sensitive to a functional CC) have been observed at the behavioral level (Roebuck-Spencer et al, 2004;Roebuck et al, 2002). Given the particular vulnerability of the CC in FAS/FASD, and presuming that dichotic listening asymmetry relies on the functional status of the CC, we expected the children with FAS in the present study to demonstrate atypical auditory lateralization during dichotic listening.…”
Section: Introductionmentioning
confidence: 78%
“…Animal studies have shown less side preference in paw use in both rat pups and adults following prenatal alcohol exposure (Moreland, La Grange, & Montoya, 2002;Zimmerberg & Riley, 1988). Some indications of deviations from typical righthandedness in prenatally alcohol-exposed human children have also been noted (Janzen, Nanson, & Block, 1995;Olsen, 1995), although not consistently (RoebuckSpencer, Mattson, Marion, Brown, & Riley, 2004;Roebuck, Mattson, & Riley, 2002). To our knowledge, however, this is the first study to characterize sensorymotor preferences and language lateralization in children with FAS and contrast them to typically developing (TD) children.…”
Section: Introductionmentioning
confidence: 80%
“…Studies of adult patients with developmental or acquired CC damage suggest that CC structural integrity is linked to cognitive performance in various domains including bimanual coordination and visual-motor integration (Berlucchi et al, 1995;Eliassen et al, 2000). Furthermore, structural CC anomalies relate to interhemispheric transfer performance deficits in several developmental disorders including dyslexia (Hynd et al, 1995) and fetal alcohol spectrum disorders (Roebuck et al, 2002). Previous magnetic resonance imaging (MRI) research indicates that the CC has a protracted growth pattern, with development continuing into adolescence, although the slope of this growth curve attenuates by young adulthood (Pujol et al, 1993).…”
mentioning
confidence: 99%
“…It has been suggested that there is both a clear increase in CC utilization throughout development and also increased utilization in children only, based on these behavioral measures (Banich et al, 2000;Marion et al, 2003). It has not been customary to examine the relationship between task performance and brain microstructure in normal development, however some studies have examined these associations in older individuals (Baird et al, 2005;Johansen-Berg et al, 2007;Roebuck et al, 2002;Sullivan et al, 2001). For example, Sullivan et al (2001) reported correlations between FA and alternating finger tapping performance in a cross-sectional analysis of healthy adults.…”
Section: Introductionmentioning
confidence: 99%